ANALISIS PEMAHAMAN MAHASISWA DALAM PEMBAGIAN HARTA WARISAN SESUAI DENGAN ILMU FIKIH DAN GEOMETRI - Endriana, Neny; Fauzi, L.Muhammad; Aziza, Yunita Huswatun (Program Studi Pendidikan Agama Islam Tarbiyah IAI Muhammadiyah Bima, 2026)
The science of faraidh is a part of muamalah fiqh that regulates the distribution of inheritance fairly and proportionally according to Islamic law. The distribution of inheritance requires not only a normative understanding of fiqh rules, but also mathematical abilities, especially in the use of fractions and proportional representation. This study aims to analyze the understanding of fourth semester students of the Mathematics Education study program at Hamzanwadi University in determining the distribution of inheritance based on fiqh and geometry. The study used a descriptive approach with a mixed method. The subjects of the study were students who had taken the fiqh of inheritance and mathematics/geometry courses. Data were collected through written tests, questionnaires, and interviews. The results of the study indicate that students' understanding of fiqh of inheritance and their geometric abilities are in the moderate category and have a significant relationship in determining the distribution of inheritance. The integration of fiqh and geometry helps students understand inheritance distribution more systematically and precisely.